The Mystery of Mrs. Christie: A Novel - Benedict, Marie (2021)
"December 1926: England unleashes the largest manhunt in its history. The object of the search is not an escaped convict or a war criminal, but the missing wife of a WWI hero, up-and-coming mystery author Agatha Christie. When her car is found wrecked, empty, and abandoned near a natural spring, the country is in a frenzy. Eleven days later, Agatha reappears, claiming amnesia. She provides no answers for her disappearance. That is...until she writes a very strange book about a missing woman, a murderous husband, and a plan to expose the truth. What role did her unfaithful husband play? And what was he not telling investigators? THE MYSTERY OF MRS. CHRISTIE explores one strong woman's successful endeavor to take her history into her own hands"--Provided by publisher.
Includes author's note, reading group guide, and a conversation with the author.
Includes bibliographical references (pages [271]-272).
Keywords: Christie, Agatha, -- 1890-1976 -- Fiction; Missing persons -- Fiction; Novelists, English -- Fiction; FICTION / Historical / World War I; FICTION / Literary; FICTION / Mystery & Detective / General; Detective and mystery fiction; Mystery fiction; Biographical fiction; Historical fiction